Instructional Adaptation and Institutional Constraints: Foreign Language Teachers' Responses to Linguistic Learning Difficulties - Inner Guevara; David Montejo Ruiz (Jurnal Educatio FKIP UNMA, 2025)
This descriptive mixed-methods case study examined methodological challenges faced by English and French teachers at Universidad Don Bosco when addressing students' linguistic learning difficulties. Twenty teachers participated between May and June 2025, completing a Likert-scale questionnaire and open-ended questions. Results revealed consistently high instructional adaptation: 95% modified teaching strategies, 90% employed multisensory approaches, and 90% provided individualized feedback. However, assessment practices showed greater variability, with only 65% reporting modifications to evaluation procedures. Thematic analysis identified four central dimensions: pedagogical differentiation, progressive scaffolding, collaborative learning tensions, and technological support. Despite these adaptations, findings revealed concrete barriers hindering sustainable inclusion: limited instructional time for differentiated strategies, heterogeneity in learning pace disrupting collaborative dynamics, and inconsistent institutional guidelines leaving teachers individually responsible for inclusive adjustments. These constraints reduce systematic application of inclusive methodologies. Discussion demonstrated alignment with Universal Design for Learning and Vygotskian scaffolding principles, while revealing assessment as a persistent bottleneck and collaborative learning as fraught with social-emotional challenges. The study concludes that fostering equitable language learning requires institutional measures including explicit adaptive assessment policies, protected pedagogical time for differentiated instruction, and sustained professional development. Findings underscore the necessity of coherent institutional frameworks supporting long-term inclusive practices in foreign language education beyond individual teacher initiative.